2014
DOI: 10.1039/c3sm52365a
|View full text |Cite
|
Sign up to set email alerts
|

Mono-molecule-layer nano-ribbons formed by self-assembly of bolaamphiphiles

Abstract: Amphiphilic molecules generally tend to organize spontaneously into spherical or cylindrical micelles/vesicles in appropriate liquid media and conditions, and seldom form two dimensional (2D) planar structures with a regular shape, due to their energetically unfavorable state. Herein, the self-assembly of a new bolaamphiphile bearing a bistriazole-pyrene unit leads to the formation of mono-molecule-layer nano-ribbons. The π-π stacking interaction between the rigid bistriazole-pyrene units and electrostatic scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…It can be clearly seen that the fibers show strong blue fluorescence when they were irradiated at 350 nm (Figs. 3c and 3d), which is consistent with the AIE 30 properties of TPE molecules because in the fibers the concentration of TPE molecules is very high. Consequently, a fluorescent supramolecular polymer was got by docking fluorescent tetraphenylethylene molecules with crown etherbased host-guest interactions.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…It can be clearly seen that the fibers show strong blue fluorescence when they were irradiated at 350 nm (Figs. 3c and 3d), which is consistent with the AIE 30 properties of TPE molecules because in the fibers the concentration of TPE molecules is very high. Consequently, a fluorescent supramolecular polymer was got by docking fluorescent tetraphenylethylene molecules with crown etherbased host-guest interactions.…”
supporting
confidence: 82%
“…11 Compared with conventional organic chromophores which display strong fluorescence in dilute 30 solutions and are non-emissive at high concentrations or in the solid state, the aggregation induced emission (AIE) properties of TPE make it act as an excellent fluorescent molecule to dock with supramolecular polymers because supramolecular polymers only form at relative high concentrations. Herein, we reported a 35 supramolecular polymer formed by crown ether-based host-guest interactions with tetraphenylethylene moieties as chromophore.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, click chemistry was used to prepare ZnTPP‐POSS. Additionally, click chemistry had another advantage in this case, because the resulting triazole ring could also enhance π–π stacking between the porphyrin moieties, leading to much more stable self‐assembled morphologies, as reported by Yin et al 13. They found that the click triazole ring could effectively enhance π‐electronic stacking interactions between pyrene molecules, leading to the formation of well‐defined nanoribbons.…”
Section: Resultsmentioning
confidence: 57%
“…Self-assembly strategies could provide innovative capabilities to biomaterials used in modern medicine and biotechnology. Recently, there has been an increased interest in the construction and design of new nano-architectural objects with well-defined shapes (nanoribbons [11], nanofibers [12], nanobelts [13], tubes [14], and rods [15]), in well-ordered and predictable sizes. Generally, a straight and efficient method for building these well-organized nanostructures is the control of supramolecular self-assembly by slightly altering environmental conditions, including solvent composition [16,17], temperature [18], pH changes [19,20], metal coordination [21], and light irradiation [22,23].…”
Section: Introductionmentioning
confidence: 99%